Assessment of Nurses Knowledge Toward Pediatrics with Anemia in the Hospitals of Al Hilla City - Yousef, Salim Amir (Indonesian Journal on Health Science and Medicine, 2025)
Anemia is a widespread condition characterized by a reduced number of red blood cells or hemoglobin concentration, which decreases the blood’s oxygen-carrying capacity. In pediatric populations, anemia represents a critical health issue that can affect growth, immunity, and overall development. Nurses play a vital role in the early detection and management of childhood anemia through proper knowledge and practice in clinical care. Despite the significance of nursing knowledge in pediatric anemia management, limited data exist regarding nurses’ awareness and understanding of childhood anemia in Al Hilla City, Iraq. Aims: This study aimed to assess nurses’ knowledge regarding pediatric anemia in hospitals of Al Hilla City and to determine the relationship between nurses’ demographic characteristics and their knowledge level. A descriptive study was conducted among 100 nurses using a self-administered questionnaire consisting of 24 items. The results showed that 60% of nurses demonstrated a low level of knowledge, 20% moderate, and 20% good knowledge regarding pediatric anemia. Statistical analysis revealed no significant relationship between nurses’ knowledge and their demographic variables, including age, gender, marital status, education level, occupation, and years of experience (p > 0.05). This study is one of the first in Babylon province to systematically assess nurses’ knowledge on pediatric anemia using a structured tool based on national guidelines. The findings highlight the need for continuous professional education and training programs to enhance nurses’ competence in pediatric anemia management and improve patient care outcomes. Highlights: More than half of the nurses (60%) demonstrated a low level of knowledge regarding pediatric anemia management. No significant relationship was found between nurses’ knowledge levels and demographic variables such as age, gender, education, or experience. Findings emphasize the need for continuous education and training programs to improve nurses’ competence in pediatric anemia care.